Sm-Eu Co-Doped BiFeO3 Nanoparticles With Superabsorption and Electrochemical Oxygen Evolution Reaction - Gu, Yanhong; Huang, Niu; Guo, Chaoyang; Liang, Yuanxi; Zhang, Weiying; Zhao, Jianguo; Zhang, Xianghui; Jia, Hong; Chen, Wanping (Frontiers in Physics, 2022)
Bi0.95Sm0.05Fe1−xEuxO3 (x = 0, 0.05, 0.10, 0.15) nanoparticles were prepared via a two-solvent sol–gel method. The X-ray diffraction (XRD) and Raman results suggested that the main phase of the samples gradually evolved from perovskite phase R3c to orthorhombic phase Pbnm with increasing Eu content and that the optical band gap gradually narrowed from 2.09 eV to 1.70 eV. Along with the structural change, the ferromagnetic properties were transformed, and interesting double hysteresis loops were observed for the sample where x = 0.1. All the bismuth ferrite (BFO) samples demonstrated extremely strong adsorbability, with the adsorption rate of refractory methyl orange reaching 90% in 5 min. These samples also exhibited superior oxygen evolution reaction (OER) performance, with a desirable onset potential of approximately 1.50 V vs. RHE. For the sample where x = 0.15, to support a current density of 100 mA/cm2, an overpotential of only 294 mV was required, which is much better than that of pure Ni foam (330 mV). More experiments are needed to verify and explore the source and mechanism of the OER performance.